The synthesis, chemical and physical characterisation of selected energetic binder systems - Alkaabi, Khalifa (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2009.